An Analysis of Love in the Piya Sutta - Phramaha Aphisit Vuḍdhissaro (Jaroenrat); Phra Sophonphatthanapundit (Dhammathas Academic Journal, 2023)
Love is a matter of all beings that cannot be avoided and is divided into four types: (1) love that arises from hate; (2) hate arises because of hate; (3) love arises because of love; (4) hate arises because of love. Therefore, it can be seen in characteristics: (1) hate is born because of love. It is the love that arises from ‘Pema,’ and characteristics (2) are that love is born from love, and (3) hate arises because of hate. It is love that arises from support until it becomes caring and then becomes love in the present which is kindness. The characteristic (4) love that arises because of hate is love arising from past bonds and mutual understanding in the present, which is Sinehā.